VoIP implementation in UiTM: a feasibility study / Saadiah Yahya and Muhd Eizan Shafiq - Yahya, Saadiah; Shafiq, Muhd Eizan (Universiti Teknologi MARA (UiTM), 2007)
Voice over internet Protocol (VoIP) offers cheaper long distance calls compared to the traditional telephone services. This study looks into the viability of VoIP implementation in Universiti Teknologi MARA (UiTM) besides the existing telephony service. The finding of the study shows that UiTM is paying heavy expenses on intercommunication calls made between its employees in the 26 campuses. This study also confirmed that VoIP is the feasible solution to reduce calls expenses. VoIP network design that integrates existing telephony system and LANs in UiTM is proposed. WANs option that affirm current and future needs of UiTM is also planned.